2008
DOI: 10.1016/j.physbeh.2008.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in zebrafish responses to cocaine withdrawal

Abstract: The acute responses to cocaine and its withdrawal contribute to cocaine dependence and potentiate relapse, with gender being one of the genetic factors affecting the outcome. Here we report that in both male and female zebrafish (Danio rerio, AB strain), an initial low-dose cocaine treatment (1.5μM, immersion) does not acutely change their behavior. The cocaine withdrawal, however, is associated with an anxiety-like state that develops earlier in female zebrafish but is more robust and persistent in males, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 75 publications
1
37
0
2
Order By: Relevance
“…The increase in dopamine, serotonin, and their metabolites following ethanol withdrawal has also been previously shown [23]. Similar to ethanol, cocaine withdrawal has also been found to induce significant increases in dopamine levels as well as decreases in the expression of the dopamine transporter gene ( zDAT ) [40]. The dopamine transporter is important for the reuptake of dopamine from the synapse [41].…”
Section: Discussionmentioning
confidence: 92%
“…The increase in dopamine, serotonin, and their metabolites following ethanol withdrawal has also been previously shown [23]. Similar to ethanol, cocaine withdrawal has also been found to induce significant increases in dopamine levels as well as decreases in the expression of the dopamine transporter gene ( zDAT ) [40]. The dopamine transporter is important for the reuptake of dopamine from the synapse [41].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, in human laboratory studies, glucose tablets decreased tobacco craving that occurred after smoking cessation (West et al 1990) and tobacco craving after overnight abstinence (West et al 1999). Other effects of drug withdrawal have been noted in rats such as increased stress responses during nicotine withdrawal (Jonkman et al 2008), increased anxiogenic effects during ETOH withdrawal (Gatch and Lal 2001;Varlinskaya and Spear 2004) or cocaine withdrawal in zebrafish (LopezPatino et al 2008a) which was later shown to be greater in males than in females (Lopez-Patino et al 2008b). Thus, behaviors that characterize the abstinence or withdrawal phase (impulsivity, motivation, stress, anxiety, reward seeking, and craving) are complex and interrelated.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9] Magguran et al demonstrated that the mating tank itself used in behavioral studies can lead to sex-specific behaviors. 10 In experiments which include the interactions of multiple zebrafish, sex and color 11,12 and age 13,14 have been shown to be determinants of behaviors, including interactions between fish and locomotion.…”
Section: Introductionmentioning
confidence: 99%